E-Commerce Trends: Shaping The Future of Retail - Mirzaeva Shirin Nodirovna; Asliev Sarvar Sharif oʻg‘li (Academia One, 2024)
The landscape of retail is continuously evolving, with e-commerce playing an increasingly significant role in shaping its future. This article explores emerging e-commerce trends that are reshaping the retail industry and transforming consumer shopping experiences. Through an analysis of current market dynamics, technological innovations, and consumer behaviors, it highlights key trends such as omnichannel retailing, mobile commerce, social commerce, and personalized shopping experiences. Additionally, it examines the impact of emerging technologies such as artificial intelligence, augmented reality, and voice commerce on the e-commerce landscape. By understanding these trends and their implications, retailers can adapt their strategies to stay competitive and meet the evolving needs and preferences of today's consumers in the digital age
Keywords: e-commerce; intelligence; retail; omnichannel retailing